Actuarial Risk Management Practices, Underwriting Risk and Performance of P & C Insurance Firms in East Africa - Angima, Caren B.; Mwangi, Mirie; Kaijage, Erasmus; Ogutu, Martin (European Scientific Journal, ESJ, 2017)
The purpose of the study was to establish the intervening effect of underwriting risk (loss ratio) on the relationship between actuarial risk management practices (ARMP) and performance of property and casualty (P & C) insurance underwriters in East Africa. Findings from primary and secondary data gathered from 82 general insurers from Kenya, Uganda and Tanzania show that there is a significant positive relationship between ARMP and non-financial performance and that loss ratio significantly mediates this relationship. The relationship with financial performance was however insignificant. The implication is that P & C insurance firms should keenly watch their loss ratios in order to improve their non-financial performance by correctly underwriting, pricing and reinsuring their risks in order to influence their claims ratio and also have a strategic claims management program in place that controls costs and leads to better firm reputation, which in turn will have ripple effect in increasing business volumes and performance. It is recommended that further empirical studies be carried out to establish other factors that especially influence financial performance.